2015
DOI: 10.1071/py14029
|View full text |Cite
|
Sign up to set email alerts
|

Oral health care in residential aged care services: barriers to engaging health-care providers

Abstract: The oral health of older people living in residential aged care facilities has been widely recognised as inadequate. The aim of this paper is to identify barriers to effective engagement of health-care providers in oral care in residential aged care facilities. A literature review was conducted using MEDline, CINAHL, Web of Science, Academic Search Complete and PsychInfo between 2000 and 2013, with a grey literature search of government and non-government organisation policy papers, conference proceedings and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 49 publications
(134 reference statements)
2
13
0
Order By: Relevance
“…Effective oral care to control plaque and promote oral healthcare includes proper tooth brushing and cleaning [37,38,41,98] and annual dental check-ups [42,75,76]. Primary care to promote oral health is crucial to help the institutionalized elderly population meet an acceptable level of oral health [37] and increase their awareness of oral healthcare [90,108]. To improve the motivation to regularly visit the dentist, an educational program should be developed for both institutionalized residents and caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Effective oral care to control plaque and promote oral healthcare includes proper tooth brushing and cleaning [37,38,41,98] and annual dental check-ups [42,75,76]. Primary care to promote oral health is crucial to help the institutionalized elderly population meet an acceptable level of oral health [37] and increase their awareness of oral healthcare [90,108]. To improve the motivation to regularly visit the dentist, an educational program should be developed for both institutionalized residents and caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…These problems are further exacerbated by residents’ physical and cognitive impairments, medical complications, and dependence on others to maintain their oral hygiene [ 14 16 ]. Several barriers to accessing oral health services have been suggested and include: accessibility of Dentists for RACF residents (particularly in rural areas); limited or non-existent referral pathways to access dental treatment; high costs of transporting residents to a Dentist; and significant issues with moving residents from familiar surroundings to be seen at an oral health clinic (particularly residents with dementia) [ 17 22 ]. Evidence also suggests that RACF staff often lack knowledge of the specific oral hygiene requirements of older people, have limited time for adequate oral care and may also have poor attitude and awareness towards oral health [ 23 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative research has indicated that older individuals perceive that some clinicians and services lack an understanding of the context in which their older patients live . Additionally, the context of aged care itself is changing, with an increasingly multidisciplinary approach to care and increasing care in the home …”
Section: Introductionmentioning
confidence: 99%